2017
DOI: 10.1007/s11033-017-4131-2
|View full text |Cite
|
Sign up to set email alerts
|

The c.29T>C polymorphism of the transforming growth factor beta-1 (TGFB1) gene, bone mineral density and the occurrence of low-energy fractures in patients with inflammatory bowel disease

Abstract: Gastrointestinal tract conditions are frequently associated with low bone mineral density and increased risk of fractures due to osteoporosis, the latter concerning particularly inflammatory bowel disease (IBD) patients. One of the candidate genes involved in osteoporosis is the transforming growth factor beta-1 (TGFB1) whose polymorphisms may be responsible for the development of this disease. The aim of this study was to analyse the frequency of TGFB1 polymorphic variants and determine the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This study included 98 patients with UC (52 females, 46 males), 100 patients with CD (49 females, 51 males) and 41 controls (20 females, 21 males). Mean values for age, height, weight, BMI, lumbar (L2–L4) BMD, femoral neck BMD, T-scores, and Z-scores, were presented according to Becherini et al [37] and compared between all groups: CD patients, UC patients and controls (Table 1) consistent with earlier reports [38,39,40]. The determined levels of vitamin D, calcium, and phosphorus are compliant with the standards and not have indicated any significant differences between the study groups as previously reported [38].…”
Section: Resultssupporting
confidence: 68%
“…This study included 98 patients with UC (52 females, 46 males), 100 patients with CD (49 females, 51 males) and 41 controls (20 females, 21 males). Mean values for age, height, weight, BMI, lumbar (L2–L4) BMD, femoral neck BMD, T-scores, and Z-scores, were presented according to Becherini et al [37] and compared between all groups: CD patients, UC patients and controls (Table 1) consistent with earlier reports [38,39,40]. The determined levels of vitamin D, calcium, and phosphorus are compliant with the standards and not have indicated any significant differences between the study groups as previously reported [38].…”
Section: Resultssupporting
confidence: 68%
“…8,9 However, other studies did not confirm this predisposition. 10 According to Frei et al, 11 the risk factors for osteoporosis in patients with CD include high daily doses of glucocorticoids and long therapy duration, young age at diagnosis (usually meaning INTRODUCTION Low bone mineral density (BMD) is an established complication in patients with inflammatory bowel disease (IBD), both Crohn disease (CD) and ulcerative colitis (UC). 1 However, data on the prevalence of skeletal system disorders in different populations of IBD patients show much variability due to different methodologies and sample sizes as well as different geographic locations.…”
mentioning
confidence: 99%
“…[57] Studies from twins and families have shown that BMD in key skeletal sites such as spine and hip was genetically determined. [8,9] A number of susceptible genes such as vitamin D receptor (VDR), [10] transforming growth factor b1 (TGFB1), [11] calcitonin receptor (CTR), [12] and osteoprotegerin gene ( OPG ), also known as tumor necrosis factor receptor superfamily member 11b (TNFRS11B) [13,14] have been identified to be involved in the pathologenesis of osteoporosis. Osteoprotegerin, a member of the tumor necrosis factor receptor superfamily, is one of the most important candidate genes in the control of bone resorption.…”
Section: Introductionmentioning
confidence: 99%